2020
DOI: 10.1063/5.0024701
|View full text |Cite
|
Sign up to set email alerts
|

Electron flow between the worlds of Marcus and Warburg

Abstract: Living organisms are characterized by the ability to process energy (all release heat). Redox reactions play a central role in biology, from energy transduction (photosynthesis, respiratory chains) to highly selective catalyzed transformations of complex molecules. Distance and scale are important: electrons transfer on a 1 nm scale, hydrogen nuclei transfer between molecules on a 0.1 nm scale, and extended catalytic processes (cascades) operate most efficiently when the different enzymes are under nanoconfine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…The Electrochemical Leaf is a nanoporous metal oxide electrode loaded with an electroactive enzyme cascade enabling it to drive rapid localized nicotinamide cofactor (NADP­(H)) recycling, making it possible to energize, control, and observe the action of these enzymes directly by dynamic electrochemical methods. When trapped in the nanopores of an indium tin oxide (ITO) electrode alongside electroactive ferredoxin-NADP + reductase (FNR), NADP­(H) dehydrogenases such as IDH (E2) are likewise rendered electroactive via efficient, highly localized recycling of NADP­(H) (Scheme A).…”
mentioning
confidence: 99%
“…The Electrochemical Leaf is a nanoporous metal oxide electrode loaded with an electroactive enzyme cascade enabling it to drive rapid localized nicotinamide cofactor (NADP­(H)) recycling, making it possible to energize, control, and observe the action of these enzymes directly by dynamic electrochemical methods. When trapped in the nanopores of an indium tin oxide (ITO) electrode alongside electroactive ferredoxin-NADP + reductase (FNR), NADP­(H) dehydrogenases such as IDH (E2) are likewise rendered electroactive via efficient, highly localized recycling of NADP­(H) (Scheme A).…”
mentioning
confidence: 99%
“…(iii) From the variation of average peak potential with pH, a Pourbaix diagram was constructed (Figure 12D). 7,234 The results led to the following conclusions. First, the FNR coverages under all conditions were much higher than that possible for a monolayer, data at pH 8 suggesting that >100 monolayer equivalents were present with the value increasing further as the pH was raised to 9.…”
Section: Overview Of the Discoverymentioning
confidence: 99%
“…The sharper shape of the reduction peak relative to the oxidation peak probably reflects the catalytic bias that is provided by the more favorable energetics for the FADH → NADP + direction (panels C and D). 7,234 Closer inspection showed that NADP + or NADPH is partially trapped in the electrode pores, as the scanrate dependence indicated a surface excess. Most significantly, despite the FAD not being covalently bound and despite the transient disruptions to the structure of the small enzyme that must occur while NADP + or NADPH bind and dissociate during each catalytic cycle, the electrochemistry was stable.…”
Section: Bidirectional Nadp(h) Recycling By Fnrmentioning
confidence: 99%
“…In photosynthesis, electrons energized by Photosystem I are used to generate NADPH from NADP + , which in turn is used for anabolic reactions, particularly the fixation of CO 2 through the Calvin cycle. The enzyme responsible, known as ferredoxin-NADP + reductase (FNR), is a small monomeric enzyme, mass 39 kDa, containing a single, non-covalently bound flavin adenine dinucleotide (FAD) cofactor [ 32 , 33 ]. During each cycle, two consecutive electrons are transferred from the small mediator protein, a [2Fe-2S] ferredoxin.…”
Section: Further Extension To Nanoconfined Multi-enzyme Cascade Processes Energized By Electrochemical Electron/hydride (Nad(p)(h) Cyclinmentioning
confidence: 99%
“…5 C, upon introduction of NADP + , the NADP + /NADPH interconversion appears as a quasi-reversible redox couple that is diffusion controlled at scan rates below 10 mV sec −1 . This result is itself significant because such electrochemistry has been sought for more than half a century [33] . It was surprising to note that binding in the ITO pores not only leaves the redox properties of FNR essentially unchanged but it has also not impeded its ability to catalyse the hydride transfer reaction, which involves the binding of NADP + at a critical position in relation to the FAD cofactor [34] .…”
Section: Further Extension To Nanoconfined Multi-enzyme Cascade Processes Energized By Electrochemical Electron/hydride (Nad(p)(h) Cyclinmentioning
confidence: 99%